Phosphodiesterase Type 5 Inhibitors and Selective Estrogen Receptor Modulators Can Prevent But Not Reverse Myofibroblast Transformation in Peyronie's Disease. Issue 10 (5th August 2020) - Ilg, Marcus M.; Stafford, Simon J.; Mateus, Marta; Bustin, Stephen A.; Carpenter, Michael J.; Muneer, Asif; Bivalacqua, Trinity J.; Ralph, David J.; Cellek, Selim
Abstract: Background: Myofibroblast transformation is a key step in the pathogenesis of Peyronie's disease (PD). Phosphodiesterase type 5 inhibitors (PDE5is) and selective estrogen receptor modulators (SERMs) can prevent the formation of fibrosis in in vitro and in vivo models of PD. However, it is unknown whether these drugs can also reverse established fibrosis. Aim: To investigate whether PDE5is and SERMs can reverse transforming growth factor beta 1 (TGF-β1)–induced myofibroblast transformation and determine the point of no return. Methods: In-Cell enzyme-linked immunosorbent assay was used to quantify TGF-β1–induced myofibroblast transformation of human primary fibroblasts isolated from tunica albuginea (TA) of patients undergoing surgery for treatment of PD. Extracellular matrix production and collagen contraction assays were used as secondary assays. Reverse transcription–quantitative polymerase chain reaction and In-Cell enzyme-linked immunosorbent assay were used to measure drug target expression. PDE5i (vardenafil) and SERM (tamoxifen) were applied at various time points after TGF-β1. Outcomes: Reversibility of myofibroblast transformation and drug target expression were investigated in a time-dependent manner in TA-derived fibroblasts. Results: Vardenafil or tamoxifen could not reverse the myofibroblast traits of alpha-smooth muscle actin expression and extracellular matrix production, whereas only tamoxifen affected collagen contraction after 72 hours of TGF-β1 treatment. Phosphodiesterase 5A and estrogen receptor (ER)-β were downregulated after 72 hours, and estrogen receptor -α protein could not be quantified. Tamoxifen could prevent myofibroblast transformation until 36 hours after TGF-β1 treatment, whereas vardenafil could prevent only 24 hours after TGF-β1 treatment. This was mirrored by downregulation of drug targets on mRNA and protein level. Furthermore, antifibrotic signaling pathways, peroxisome proliferator-activated receptor gamma and betaglycan (TGFB receptor III), were significantly downregulated after 36 hours of TGF-β1 exposure, as opposed to upregulation of profibrotic thrombospondin-1 at the same time point. Clinical Translation: This study suggests that using PDE5is and SERMs might only help for early-phase PD and further highlights the need to test drugs at the appropriate stage of the disease based on their mechanism of action. Strengths & Limitations: The study uses primary human TA-derived fibroblasts that enhances translatability of the results. Limitations include that only 1 example of PDE5i- and SERM-type drug was tested. Time course experiments were only performed for marker expression experiments and not for functional assays. Conclusion: This is the first study to demonstrate that timing for administration of drugs affecting myofibroblast transformation appears to be vital in in vitro models of PD, where 36 hours of TGF-β1 treatment can be suggested as a "point of no return" for myofibroblast transformation.